1999
DOI: 10.1021/ic980826q
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear 1,2,4,5-Tetraimino-3,6-diketocyclohexane Bis[bis(Bipyridine)ruthenium(II)] Redox Series

Abstract: The reaction of the [Ru(bpy)2(MeOH)2]2+ cation (bpy = 2,2'-bipyridine) with 1,2,4,5-tetraaminobenzene in the presence of trace water and oxygen yields the cation [(bpy)2Ru(1,2,4,5-tetraimino-3,5-diketocyclohexane)Ru(bpy)2]4+. This binuclear species undergoes ligand-based reductions, giving the 3+ and 2+ charged species. The X-ray structure, electrochemistry, ZINDO calculations, and NMR, ESR, UV/vis, and IR spectra were analyzed where possible, giving an electronic model of the binuclear species and some of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 72 publications
4
40
0
Order By: Relevance
“…[44][45][46][47][48][49][50] The present report represents one of only a handful of structures that have been obtained through selective diastereoisomer isolation prior to crystal growth. [13,19,[51][52][53] Electrochemical and UV/Vis/NIR spectral characterisation: …”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46][47][48][49][50] The present report represents one of only a handful of structures that have been obtained through selective diastereoisomer isolation prior to crystal growth. [13,19,[51][52][53] Electrochemical and UV/Vis/NIR spectral characterisation: …”
Section: Resultsmentioning
confidence: 99%
“…We attribute these absorptions to metal-to-ligand charge transfer (MLCT) transitions from d orbitals of the electronrich metal centers with d 6 (Re I ) or d 10 (Cu I ) configuration to the p* orbital of the o-quinonediimine p system which is largely concentrated at the coordinating a-diimine part. Such longwavelength MLCT transitions have been observed for numerous a-diimine complexes of ] however, the very high intensities with e = 12 500 m À1 cm À1 for the Cu I complex and even 20 100 m À1 cm À1 for the Re I compound of L o is characteristic for complexes of p-and of o-quinonediimines as has been reported before mainly for ruthenium(ii) compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Using the all-nitrogen compound azophenine L p , a long established p-quinonoid compound [8] with a hardly explored ligand potential in coordination chemistry, [9,10] we have previously shown that coordination of phosphine-stabilized copper(i) can cause tautomerization to the chelating o-quinonoid tautomer L o (Scheme 2), supported by interionic ringforming hydrogen bonding between the newly o-positioned NHPh substituents with one fluorine atom of the BF 4 À counterion. [11] Metal-induced tautomerization is a phenomenon that has been discussed especially in connection with Pt II ±nucleobase interaction where stabilization of the ™wrong∫ tautomer could lead to mispairing in nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The remarkable properties that such ligands impart to their metal complexes make such compounds useful in a variety of fields, such as homogenous catalysis, [7] supramolecular chemistry, [5,8] coordination polymers, [9,10] and as bridging ligands in combination with redox active metal centers such as ruthenium. [11][12][13][14] The last field has gained tremendous attention in recent years because of ambiguities arising in oxidation-state formulations also with "organometallic-type" non-innocent ligands. [15] In addition, the creation of quinone-based molecular magnets is a lively field of research that has produced many interesting results.…”
mentioning
confidence: 99%